2008
DOI: 10.1073/pnas.0710434105
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 is highly expressed in pancreatic α-cells and influences secretion and survival

Abstract: In pancreatic ␤-cells, uncoupling protein 2 (UCP2) influences mitochondrial oxidative phosphorylation and insulin secretion. Here, we show that ␣-cells express significantly higher levels of UCP2 than do ␤-cells. Greater mitochondrial UCP2-related uncoupling was observed in ␣-cells compared with ␤-cells and was accompanied by a lower oxidative phosphorylation efficiency (ATP/O). Conversely, reducing UCP2 activity in ␣-cells was associated with higher mitochondrial membrane potential generated by glucose oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 45 publications
2
60
1
Order By: Relevance
“…Large cells were selected as b-cells, as they are likely to be insulin-positive ( Supplementary Fig. S1, available in the online version of the Journal of Endocrinology at http:// joe.endocrinology-journals.org/cgi/content/full/JOE-09-0117/DC1) and have been shown to be larger than other cell types (Göpel et al 1999, Diao et al 2008. In both WT and UCP2KO b-cells, we did not find a significant increase in ROS formation post-STZ treatment in either genotype; however, we did observe a significant increase in ROS formation when untreated WT and UCP2KO controls were compared (Fig.…”
Section: Impact Of Ucp2 On Ros Production Before and After Stz Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Large cells were selected as b-cells, as they are likely to be insulin-positive ( Supplementary Fig. S1, available in the online version of the Journal of Endocrinology at http:// joe.endocrinology-journals.org/cgi/content/full/JOE-09-0117/DC1) and have been shown to be larger than other cell types (Göpel et al 1999, Diao et al 2008. In both WT and UCP2KO b-cells, we did not find a significant increase in ROS formation post-STZ treatment in either genotype; however, we did observe a significant increase in ROS formation when untreated WT and UCP2KO controls were compared (Fig.…”
Section: Impact Of Ucp2 On Ros Production Before and After Stz Treatmentmentioning
confidence: 99%
“…An inner mitochondrial protein known as uncoupling protein-2 (UCP2), is shown to be expressed in pancreatic b-cells (Chan et al 1999) and a-cells (Diao et al 2008), as well as other tissues (Fleury et al 1997) and has been shown to contribute to mitochondrial proton leakage (Fink et al 2002, Affourtit & Brand 2008. In the b-cell, such activity may uncouple glucose metabolism from ATP synthesis thereby impeding the mechanism that triggers insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 UCP2 was thought to be a negative regulator of reactive oxidative species (ROS) production and a physiological brake for ROS signaling owing to its possible role in reducing the protonic membrane potential of mitochondria. 8 UCP2 attenuates oxidative stress and has a protective role in mouse cardiomyocytes, 9 neuronal cells, 10,11 pancreatic alpha cells, 12 and macrophages or monocytes 13 in a transgenic mouse model. Overexpression of UCP2 produced a reduced inflammatory response following LPS treatment.…”
mentioning
confidence: 99%
“…Glucagon-and insulin-positive areas were also determined using ImagePro Plus. Immunofluorescent staining of dispersed islet cells were performed as previously described (17).…”
Section: Immunohistochemistry and Immunofluorescencementioning
confidence: 99%